Association of Polycyclic Aromatic Hydrocarbons Urine Metabolites with Type 1 Diabetes - Roya Kelishadi; Silva Hovsepian; Mohammad Mehdi Amin; Nafiseh Mozafarian; Sara Sedaghat; Mahin Hashemipour (Journal of Diabetes Research, 2023)
Purpose. Polycyclic aromatic hydrocarbons (PAHs) are believed to be a possible factor in the development of cancer, ischemic heart disease, obesity, and cardiovascular disease. The objective of this study was to explore the association between certain metabolites of urinary PAH and type 1 diabetes (T1D). Methods. In Isfahan City, a case-control study was carried out involving 147 T1D patients and an equal number of healthy individuals. The study measured the levels of urinary metabolites of PAHs, specifically 1-hydroxynaphthalene, 2-hydroxynaphthalene, and 9-hydroxyphenanthrene, in both the case and control groups. The levels of these metabolites were then compared between the two groups to assess any potential association between the biomarkers and T1D. Results. The mean (SD) age of participants in the case and control groups was 8.4 (3.7) and 8.6 (3.7) years old, respectively, (P>0.05). In terms of gender distribution, 49.7% and 46% of participants in the case and control groups were girls, respectively (P>0.05). Geometric mean (95% CI) concentrations were: 36.3 (31.4-42) μg/g creatinine for 1-hydroxynaphthalene, 29.4 (25.6-33.8) μg/g creatinine for 2-hydroxynaphthalene, and 72.26 (63.3-82.5) μg/g creatinine for NAP metabolites. After controlling for variables such as the child’s age, gender, maternal and paternal education, duration of breastfeeding, exposure to household passive smoking, formula feeding, cow’s milk consumption, body mass index (BMI), and five dietary patterns, it was observed that individuals in the highest quartile of 2-hydroxynaphthalene and NAP metabolites had a significantly greater odd ratio for diabetes compared to those in the lowest quartile (P<0.05). Conclusion. Based on the findings of this study, it is suggested that exposure to PAH might be linked to an increased risk of T1D in children and adolescents. To clarify a potential causal relationship related to these findings, further prospective studies are needed.